Exploiting direct link in EH based two-way DF half-duplex relaying network: Outage probability analysis - Phu Tran Tin; Minh Tran; Tran Thanh Trang (Bulletin of Electrical Engineering and Informatics, 2020)
Relay communication is considered as a popular solution for expanding the coverage, increasing the transmission capacity and reducing the power consumption of the communication networks. In this paper, we proposed and investigated the two-way decode-and-forward (DF) half-duplex (HD) relaying network with the direct link between two sources S1 and S2. Firstly, the system model, energy harvesting (EH) and information transmission (IT) are presented. The closed-form analytical expression of the system outage probability (OP) is analyzed and derived in the next stage. Finally, the correctness of the analytical expressions is verified by Monte Carlo simulation. The research results show that the analytical and simulation are the same in connection with the primary system parameters.